Liver Transplantation Prevents Progressive Neurological Impairment in Argininemia - Santos-Silva, E. (2013)
Argininemia is a rare hereditary disease due to a deficiency of hepatic arginase, which is the last enzyme of the urea cycle and hydrolyzes arginine to ornithine and urea. The onset of the disease is usually in childhood, and clinical manifestations include progressive spastic paraparesis and mental retardation. Liver involvement is less frequent and usually not as severe as observed in other UCDs. For this reason, and because usually there is a major neurological disease at diagnosis, patients with argininemia are rarely considered as candidates for OLT despite its capacity to replace the deficient enzyme by an active one. We report on long-term follow-up of two patients with argininemia. Patient 1 was diagnosed by the age of 20 months and despite appropriate conventional treatment progressed to spastic paraparesis with marked limp. OLT was performed at 10 years of age with normalization of plasmatic arginine levels and guanidino compounds. Ten years post-OLT, under free diet, there is no progression of neurological lesions. The second patient (previously reported by our group) was diagnosed at 2 months of age, during a neonatal cholestasis workup study. OLT was performed at the age of 7 years, due to liver cirrhosis with portal hypertension, in the absence of neurological lesions and an almost-normal brain MRI. After OLT, under free diet, there was normalization of plasmatic arginine levels and guanidino compounds. Twelve years post-OLT, she presents a normal neurological examination. We conclude that OLT prevents progressive neurological impairment in argininemia and should be considered when appropriate conventional treatment fails.